Simple, Sensitive, and Selective High Performance Liquid Chromatographic (HPLC) Method for the Determination of Buturon in Herbal Tea, Dried Blueberry, and Cranberry Samples and Evaluation of Its Stability in Gastric Conditions - Ozzeybek, Gozde; Erarpat, Sezin; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
This study proposed a novel analytical method for the determination of buturon at trace levels in herbal tea, dried blueberry, and cranberry samples by high performance liquid chromatography with ultraviolet detection (HPLC-UV). In order to lower the detection limits, some parameters such as the analytical wavelength, mobile phase content, mobile phase flow rate, and injection volume were optimized. Under the optimum conditions, the limit of detection (LOD) and limit of quantitation (LOQ) were determined to be 9.5 and 32 mu g/kg. The relative standard deviations for the lowest concentration in the calibration plot were evaluated to be 7.2%. The proposed method was linear across the working range from 0.05 to 168 mg/kg. Recovery studies were performed to confirm the accuracy and applicability of the developed method. Appreciable recovery results for herbal tea, dried blueberry, and cranberry samples were obtained in the range between 88 and 118%. The stability of buturon in simulated gastric fluid was also investigated to characterize its properties in the human body. There was no transformation of the analyte in the simulated gastric medium.
Keywords: Buturon; high performance liquid chromatography (HPLC) herbal tea; dried blueberry; dried cranberry; simulated gastric juice; SOLID-PHASE-EXTRACTION; PHENYL-UREA HERBICIDES; GAS-CHROMATOGRAPHY; PROPANIL HERBICIDES; PESTICIDES; WATER; MICROEXTRACTION; DERIVATIZATION; DEGRADATION; POLYMER; Chemistry